2016
DOI: 10.1093/bja/aew272
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Mallampati evaluation in neutral or extended cervical spine positions: a retrospective observational study of 80 000 patients

Abstract: These articles were published by mistake in the May 2016 issue of BJA due to an administrative error. They were supposed to go into this special issue on Airway Management. The articles can be accessed free of charge at the following link

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…). After detailed assessment, we included 133 studies (127 cohort type and six case–control) involving 844,206 participants . Of the 133 studies, there were six for the Mallampati test, 105 for the modified Mallampati test, six for Wilson risk score, 52 for thyromental distance, 18 for sternomental distance, 34 for the mouth opening test and 30 for the upper lip bite test.…”
Section: Resultsmentioning
confidence: 99%
“…). After detailed assessment, we included 133 studies (127 cohort type and six case–control) involving 844,206 participants . Of the 133 studies, there were six for the Mallampati test, 105 for the modified Mallampati test, six for Wilson risk score, 52 for thyromental distance, 18 for sternomental distance, 34 for the mouth opening test and 30 for the upper lip bite test.…”
Section: Resultsmentioning
confidence: 99%
“…22 If visual inspection or palpation fails to identify the CTM location with certainty, it should be identified using ultrasonography and marked, 22,23 with the patient's neck in an extended position. The patient can subsequently be positioned Table 1 Published predictors of difficult tracheal intubation using direct laryngoscopy Predictors of difficult laryngoscopy and tracheal intubation using direct laryngoscopy [11][12][13]16,[25][26][27][28][29][30][31] • Age [ 46 yr…”
Section: The Enhanced Airway Evaluationmentioning
confidence: 99%
“…Recommendations for the anticipated difficult airway DL or intubation. Whether obesity alone predicts difficult laryngoscopy/intubation continues to be controversial, with some studies reporting an association, 15,29,31,39,[192][193][194][195] and others not. 11,25,191,[196][197][198] No studies have yet reported obesity to be a risk factor for difficult or failed VLfacilitated tracheal intubation, although one study has reported a thick neck to be associated with failed HA-VLfacilitated tracheal intubation.…”
Section: Post-proceduresmentioning
confidence: 99%
“…Although efforts have been made to find reliable predictive tests for difficult airways [12][13][14], these tests may frequently fail to predict the difficulty.…”
Section: Adequate Planningmentioning
confidence: 99%